Generation Z and CRISPR: Measuring information processing using animated infographics - Maria A Martinez; Jessica Holt; Alexa Lamm; Abigail Borron (Journal of Applied Communications, 2021)
CRISPR gene-editing technology, as it relates to food, has the potential to revolutionize the agricultural industry. Currently, 40% of global consumers are categorized as Generation Z. Gen Zer’s are digital natives and use Instagram to discover new products; therefore, it is important to understand the most effective communications strategies to engage this segment of consumers with scientific information that will allow for informed decision-making regarding CRISPR technology. Infographics are a form of data visualization that can be used in a static or animated form. Previous studies have shown animated infographics to garner greater attention from respondents. Using the Heuristic-Systematic Processing Model (HSM) and the Risk Information Seeking and Processing (RISP) model as the guiding theoretical framework, this study used an experimental design to investigate respondents’ information recall ability of CRISPR information using infographics. The results from the current study indicated respondents heuristically processed the information about CRISPR displayed to them through an infographic, as statistically significant differences were measured between the animated infographic treatment group and the respondent’s recall ability on only 2 of the 3 recall questions asked. The exploration of demographic characteristics found a moderating effect on recall ability for only the static treatment group and political ideology. Key findings in the current research suggest the implementation of animated infographics may aid in more effective agricultural messaging if kept to one point of information and have a source of credibility.
Keywords: infographics; generation z; crispr; instagram